Analysis of the Competitiveness of Indonesian Clove Exports to the Main Destination - Barus, Rusyqy Fuad Arsa; Rachmina, Dwi; Hidayat, Nia Kurniawati (Universitas Panji Sakti, 2025)
Indonesia is the largest producer of cloves and one of the largest exporters of cloves in the world. In 2023, Indonesia's clove production reached 135,178 tons, with an export value of US 99,605,682. Indonesia's clove trade balance has been in surplus since 2017-2023. Between 2021 and 2022, there was a decrease in the export value of cloves to major destination countries. This was caused by Indonesia's high demand for cloves due to the presence of the kretek cigarette industry in the country. The aim of this research is to analyze the competitiveness of Indonesian cloves in its main export markets and examine the factors that influence the export of cloves to these key destination countries. This study uses Revealed Comparative Advantage (RCA) analysis, Export Product Dynamic (EPD), X-Model, and panel data regression. From 2011 to 2023, Indonesia had a comparative advantage in all destination countries. The highest comparative advantage was found in the United Arab Emirates, while the lowest was in Singapore. Indonesia has a competitive advantage in four countries: Bangladesh, India, Pakistan, and the United Arab Emirates, and these countries show optimism for the development of exports. The variables of Indonesian clove production and export prices have a positive and significant effect on the export value of Indonesian cloves.